2019
DOI: 10.3389/fphar.2019.00040
|View full text |Cite
|
Sign up to set email alerts
|

CRP-Induced NLRP3 Inflammasome Activation Increases LDL Transcytosis Across Endothelial Cells

Abstract: The NLRP3 inflammasome, a multiprotein cytosolic complex that activates the IL-1 family of cytokines, plays an important role in atherosclerosis (AS). High-sensitivity c-reactive protein (hs-CRP) is widely recognized as a major cardiovascular risk predictor and recent studies name NLRP3 as a predictor of CRP levels. Mounting evidence has indicated that subendothelial retention of apolipoprotein B100-containing lipoproteins, such as low-density lipoprotein (LDL), is the initial step of atherogenesis, and is usu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(35 citation statements)
references
References 29 publications
(41 reference statements)
2
30
1
Order By: Relevance
“…Therefore, autophagy alteration could be an additional mechanism through which C-reactive protein can possibly promote endometrial cancer development and progression. An interesting study was performed by Bian et al who investigated impact of C-reactive protein on human umbilical cord cells [45]. Western blot analyses revealed CRP induced expression and activation of NLRP3 (NOD-like receptor family, pyrin domain-containing protein 3) and its product, IL-1β, through FcgR/NF-κB (nuclear factor κB) pathway [45].…”
Section: Increased Crp As a Bad Prognostic Sign -Potential Mechanismmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, autophagy alteration could be an additional mechanism through which C-reactive protein can possibly promote endometrial cancer development and progression. An interesting study was performed by Bian et al who investigated impact of C-reactive protein on human umbilical cord cells [45]. Western blot analyses revealed CRP induced expression and activation of NLRP3 (NOD-like receptor family, pyrin domain-containing protein 3) and its product, IL-1β, through FcgR/NF-κB (nuclear factor κB) pathway [45].…”
Section: Increased Crp As a Bad Prognostic Sign -Potential Mechanismmentioning
confidence: 99%
“…An interesting study was performed by Bian et al who investigated impact of C-reactive protein on human umbilical cord cells [45]. Western blot analyses revealed CRP induced expression and activation of NLRP3 (NOD-like receptor family, pyrin domain-containing protein 3) and its product, IL-1β, through FcgR/NF-κB (nuclear factor κB) pathway [45]. Liu et al examined tumour samples of 31 women with endometrial cancer, showing that NLRP3 overexpression is significantly associated with increased proliferation, migration and invasion of EC cells [46].…”
Section: Increased Crp As a Bad Prognostic Sign -Potential Mechanismmentioning
confidence: 99%
“…Interestingly, the SAA proteins are known to activate the inflammasome in macrophages, neurons, and other cell types [61,62]. Similarly, C-reactive protein activates the inflammasome in the endothelial cells [63]. As a critical component of the inflammatory process, the acute-phase response amplifies tissue inflammation, exacerbates tissue damage, and causes metabolic dysregulation that enhances disease complications.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was found that CRP can upregulate the activity of NF‐κB in VECs, induce the expression of NLRP3 and pro‐IL‐1β, as well as promote the activation of the NLRP3 inflammasome and IL‐1β maturation by increasing ROS levels. In an in vitro model of trans‐cellular LDL transport, VECs and CRP were incubated for 24 h, and the expression of proteins involved in the NLRP3 inflammasome activation signaling pathway was upregulated, indicating that NLRP3 inflammasome activation is involved in CRP‐mediated trans‐VEC LDL transport, promoting the inflammatory response of VECs (Bian et al, 2019).…”
Section: Regulatory Effects Of the Nlrp3 Inflammasome In Primary Cells During Vrmentioning
confidence: 99%